A case of B.1.1.7 SARS-CoV-2 UK strain with an atypical radiological presentation - Doğan, Emrah; Tapan, Utku; Oral Tapan, Özge; Alaşan, Fatih; Olcay, Sabri Serhan; Çınar Olcay, Tuğba (Monaldi Archives for Chest Disease, 2021)
The new UK strain was first described in December 2020. It was seen for the first time in Turkey in February 2021. It is not yet known whether the new strain has different CT patterns compared to the classical type. We present a 68-years-old male patient with an atypical CT presentation in which GGOs are gathered around the areas of paraseptal emphysema accompanied by CT and clinical findings. This involvement is an unexpected pattern because of the atypical distribution of the GGO.